Fatores ambientais e a autorregulação emocional deficiente em crianças e/ou adolescentes com transtorno do déficit de atenção e hiperatividade- tdah - Serra, Lilian Grecu [UNIFESP] (2015)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopment disorder of high prevalence that begins in childhood and can continue until adulthood. It is considered a multifactorial disorder whose environmental and genetic factors can be connected directly in their incidence. It is known today that the basis of ADHD falls on the neurobiological nature, genetics and neurochemistry, but the expression of inherited patterns is also modulated by environmental factors through epigenetic processes. Objective: to Investigate and analyze the possible variables related to environmental factors that may contribute effectively to the occurrence of the attention deficit hyperactivity disorder-ADHD. Method: this study used the following instruments: Script of questions, Family-RAF Resource inventory, The Coelho-Savassi Family Risk Scale, Scale of Adverse Events, Self-Report Questionnarie-SRQ-20, Stress Symptoms Inventory for Adult- and Child Behavior Checklist-CBCL. The data obtained were analyzed according to the guidelines of their respective authors; descriptive statistical analysis was used for the characterization of the variables found. Results: The most important adverse events are related to the absence of the father (62%) and mother (58%). The presence of alcohol, drugs and marital brawls have been identified in part of the families studied, as well as a significant number of cases of stress and emotional factors related to parents. The difficulties related to parental support were also found in the present study. There was still a high rate (87%) of emotional self-regulation deficient in children who were evaluated. Conclusion: environmental factors such as: Adversity, lack of family support, family cohesion and parental use of alcohol/drugs by parents, can be directly linked to cases of ADHD. It is possible that episodes of stress and psychiatric problems of parents may be related to deficiency in emotional self-regulation found in children.